Diversity-oriented synthesis of 17-spirosteroids - Laroche, Benjamin; Bouvarel, Thomas; Louis-Sylvestre, Martin; Nay, Bastien (Beilstein Journal of Organic Chemistry, 2020)
A diversity-oriented synthesis (DOS) approach has been used to functionalize 17-ethynyl-17-hydroxysteroids through a one-pot procedure involving a ring-closing enyne metathesis (RCEYM) and a Diels–Alder reaction on the resulting diene, under microwave irradiations. Taking advantage of the propargyl alcohol moiety present on commercially available steroids, this classical strategy was applied to mestranol and lynestrenol, giving a collection of new complex 17-spirosteroids.
Keywords: diversity-oriented strategy; 17-ethynyl-17-hydroxysteroids; ring-closing enyne metathesis; spirosteroids; steroids